Cultural Ambivalence About Divorce in Children and Adults’ Discourses [Ambivalências Culturais Sobre O Divórcio Nos Discursos Das Crianças E Dos Adultos] [Ambivalencias Culturales Sobre el Divorcio en Discursos de Niños, Niñas y Adultos] - Vergara-Del Solar, A (Revista Latinoamericana de Ciencias Sociales, 2022)
This article illustrates some of the cultural ambivalence about parental divorce in the discourse produced by children and adults using conceptual tools provided by British cultural studies. Triangular group interviews were conducted with people from different socio-economic strata in Santiago, Chile and discourse analysis was conducted. The results evidenced discourses with more fixed and conventional articulations that are coherent with the dominant modern prototypical family model. There were also more oscillating resopnses, which showed re-articulations and the presence of residual and emerging cultural forms alongside dominant discourses. © 2022 Revista Latinoamericana de Ciencias Sociales, Ninez y Juventud. All rights reserved.